Menyelidiki Kesulitan dan Strategi Pelajar EFL dalam Keterampilan Menulis Akademik: Studi Kualitatif - Riadil, Ikrar Genidal (ELP (Journal of English Language Pedagogy), 2023)
Writing is an important aspect of language development and should be of primary interest and concern to teachers, students, and academics. The researchers found a research gap by observing that in the field of research, there are a lot of students who have difficulties in writing and still do not know the strategy to solve their problems. This study aims to identify the writing difficulties that students face, as well as strategies for overcoming those difficulties. A descriptive qualitative research method was used in this study. The researchers used a questionnaire to collect the data. The participants were twenty-five 5th semester students from the English department, Universitas Tidar in the academic year 2021/2022. The result of the study showed that nine students encountered difficulties in grammar, eight students had problems with an academic style, and three students encountered difficulties in the organization of writing and vocabulary. Furthermore, independent writing is one of the most common strategies employed by students. Understanding the difficulties of students and strategies for writing skills will have a good impact on the outcome of the learning process.